Source-Grid Coordinated Planning Considering Network Node Inertia Level Differences Under Coal-Fired Power Unit Retirement - Yutao Xu; Chao Sun; Lu Liu; Houyi Zhang; Wenxia Liu; Zhukui Tan (Applied Sciences)
How to consider the differentiated inertia levels of each node during the retirement of coal-fired power units to ensure system frequency security is a current research challenge. This paper proposes a source-grid collaborative planning method that accounts for the differentiated inertia levels of network nodes during the coal-fired power unit retirement. First, a frequency response model based on a multi-machine equivalence approach and a differentiated inertia level model based on a virtual synchronous machine transformation approach for each network node are established, and a node inertia constraint model can be obtained. Next, the characteristics of coal-fired power unit retirement are analyzed. Subsequently, a source-grid collaborative planning model that considers the differentiated inertia levels of network nodes during the retirement of coal-fired power units is proposed. Finally, the feasibility and effectiveness of the coal-fired unit retirement and source-grid planning model are validated by the IEEE 24-node case and a real-region case. The case study analysis indicates that compared with the conventional planning scheme, the planning scheme considering the node inertia level constraints has less retired thermal unit capacity, more installed capacity of new thermal units, and a uniform distribution of inertia levels.